2015
DOI: 10.1186/s40200-015-0167-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of topical olive oil on the healing of foot ulcer in patients with type 2 diabetes: a double-blind randomized clinical trial study in Iran

Abstract: BackgroundDiabetic Foot Ulcer (DFU) is the most costly and devastating complication of diabetes mellitus which can lead to infection, gangrene, amputation, and even death if the necessary care is not provided. Nowadays, some herbal products have shown therapeutic effects on healing of DFU. So, this study aimed to assess the effects of topical olive oil on the healing of DFU.MethodsThis double-blind randomized clinical trial study was conducted in Diabetes Clinic of Ahvaz Golestan hospital, Iran, in 2014. Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 31 publications
5
55
0
1
Order By: Relevance
“…Therefore, it was difficult to be certain of the robustness of the findings. One small RCT on topical olive oil reported beneficial effect on complete healing rate ( P = .003) at 4 weeks in a per‐protocol analysis . In addition to the study where unsupervised exercise was investigated in no‐option ischaemia, we also found another nonblinded study on foot exercise, which reported a benefit at 12 weeks in a per‐protocol analysis .…”
Section: Systemic Including Medical and Nutritional Therapiesmentioning
confidence: 85%
“…Therefore, it was difficult to be certain of the robustness of the findings. One small RCT on topical olive oil reported beneficial effect on complete healing rate ( P = .003) at 4 weeks in a per‐protocol analysis . In addition to the study where unsupervised exercise was investigated in no‐option ischaemia, we also found another nonblinded study on foot exercise, which reported a benefit at 12 weeks in a per‐protocol analysis .…”
Section: Systemic Including Medical and Nutritional Therapiesmentioning
confidence: 85%
“…The present results demonstrate that the therapeutic safety profile of topical treatment with olive oil is equivalent to that of HOFA treatments. No adverse effects were observed in our olive oil group, similar to findings of other studies on the topical application of olive oil on healthy skin and diabetic foot ulcers . Olive oil can therefore be considered a safe product for topical application.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules endow olive oil with exceptional skincare properties, improving hydration and exerting a protective, emollient, and regenerating action . Experimental studies have demonstrated that olive oil exerts beneficial effects on the skin and promotes ulcer healing . Nevertheless, there has been no research on the efficacy of topical olive oil application for PU prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid formula Oral Antimicrobial and pro-angiogenic properties [108] Sida cordifolia Linn. Hydrogel Local Antimicrobial and pro-angiogenic properties [109] Polyherbal Cream Local Antimicrobial and pro-angiogenic properties [117] Olive oil Topic Local Antimicrobial and pro-angiogenic properties [118] Nigella sativa Gel Local Antimicrobial and pro-angiogenic properties [119] Neem and Haridra Liquid formula, gel Local, oral Antimicrobial and pro-angiogenic properties [120] Hypericum and neem oil Unguent Local Antimicrobial and pro-angiogenic properties [110] Tragia involucrata In vitro study -Antimicrobial properties [111,121] Oral doses of extracts of citrus peel (lemon, grapefruit, and orange) in diabetic rats were evaluated to examine if these extracts could be beneficial in the regeneration of ulcers. The authors obtained positive outcomes in the reduction of glucose in the blood and wound healing rate and introduced this therapy as a potential therapeutic alternative for the treatment of DFUs [108].…”
Section: Plant Extract Presentation Route Of Administration Action Rementioning
confidence: 99%
“…Kiwi fruits also showed antimicrobial and pro-angiogenic features on neuropathic DFUs [113]. Finally, the impact of topical olive oil on the healing of DFUs showed a significant decrease in the DFU area [118], whereas a combination of the neem and Haridra plants to treat wounds that do not normally heal conferred healing effects when combining neem in its topical form with Haridra via oral presentation [120].…”
Section: Plant Extract Presentation Route Of Administration Action Rementioning
confidence: 99%